Combination of targeted monitoring and Breeding Bird Survey data improves population trend estimation and species distribution modeling for the Common Nighthawk. Issue 2 (8th May 2021) - Knight, Elly C; Smith, Adam C; Brigham, R Mark; Bayne, Erin M
Abstract: Standardized monitoring is critical for conservation because reliable survey data are used to inform the necessity, type, and effectiveness of conservation actions. Many of the avian monitoring data used for conservation are collected by "comprehensive" programs that survey for all species observed; however, there are some species that have low availability for detection during comprehensive surveys and are instead monitored with targeted programs. Unfortunately, those targeted programs are rarely evaluated relative to existing programs and management objectives to inform allocation of effort. We assessed the statistical performance of the comprehensive North American Breeding Bird Survey (BBS), the targeted Canadian Nightjar Survey (CNS), and the two programs combined for the Common Nighthawk ( Chordeiles minor ). First, we used parameters from the existing datasets to simulate population declines and determined the probability of detecting those declines. Analyses that combined both datasets resulted in higher probability of detecting a 30% population decline (BBS: 38%, CNS: 64%, combined: 69%). Next, we built probability of occurrence models and assessed the predictive performance of those models. Combined analyses had similar predictive performance to the CNS and moderated poor performance of the BBS in the north (mean Cohen's kappa; BBS: 0.40, CNS: 0.46, combined: 0.50). Our results suggest that data from targeted monitoring is important for evaluation of Common Nighthawk population trend and habitat relationships but is best combined with BBS data. Comprehensive and targeted monitoring programs may be better when considered together, and exploration of data combination should become the rule, not the exception. We suggest that the framework we present can be used as a starting point for evaluating targeted monitoring programs relative to defined objectives and existing programs, with the potential to explore hypothetical management scenarios. Lay Summary: Not all species are well detected during "comprehensive" bird surveys like the Breeding Bird Survey. Targeted monitoring at particular times of day or in specific locations can help detect those species and help wildlife managers conserve them. The Common Nighthawk is a crepuscular bird that is poorly detected during comprehensive dawn surveys. We showed that the targeted Canadian Nightjar Survey improves the precision of Common Nighthawk population trends and accuracy of habitat predictions. Combining information from the Breeding Bird Survey and the Canadian Nightjar Survey can further improve population trend estimates and habitat predictions. Our study suggests that targeted monitoring can be important for some species and that combining it with comprehensive monitoring is important for evaluating existing and proposed conservation programs.